Sodium bicarbonate supplementation does not improve running anaerobic sprint test performance in semiprofessional adolescent soccer players - dos Santos Guimarães, R.; de Morais Junior, A. C.; Schincaglia, R. M.; Saunders, B.; Pimentel, G. D.; Mota, J. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Ergogenic strategies have been studied to alleviate muscle fatigue and improve sports performance. Sodium bicarbonate (NaHCO3) has improved repeated sprint performance in adult team-sports players, but the effect for adolescents is unknown. The aim of the present study was to evaluate the effect of NaHCO3 supplementation on repeated sprint performance in semiprofessional adolescent soccer players. In a double-blind, placebo-controlled, crossover trial, 15 male semiprofessional adolescent soccer players (15 ± 1 years; body fat 10.7 ± 1.3%) ingested NaHCO3 or a placebo (sodium chloride) 90 min before performing the running anaerobic sprint test (RAST). A countermovement jump was performed before and after the RAST, and ratings of perceived exertion, blood parameters (potential hydrogen and bicarbonate concentration), and fatigue index were also evaluated. Supplementation with NaHCO3 promoted alkalosis, as demonstrated by the increase from the baseline to preexercise, compared with the placebo (potential hydrogen: +0.07 ± 0.01 vs. -0.00 ± 0.01, p < .001 and bicarbonate: +3.44 ± 0.38 vs. -1.45 ± 0.31 mmol/L, p < .001); however, this change did not translate into an improvement in RAST total time (32.12 ± 0.30 vs. 33.31 ± 0.41 s, p = .553); fatigue index (5.44 ± 0.64 vs. 6.28 ± 0.64 W/s, p = .263); ratings of perceived exertion (7.60 ± 0.33 vs. 7.80 ± 0.10 units, p = .525); countermovement jump pre-RAST (32.21 ± 3.35 vs. 32.05 ± 3.51 cm, p = .383); or countermovement jump post-RAST (31.70 ± 0.78 vs. 32.74 ± 1.11 cm, p = .696). Acute NaHCO3 supplementation did not reduce muscle fatigue or improve RAST performance in semiprofessional adolescent soccer players. More work assessing supplementation in this age group is required to increase understanding in the area.